Thailand - Assessment of Observance of the CPSS-IOSCO Principals for Financial Market Infrastructures : BAHTNET and TSD - International Monetary Fund (World Bank, Washington, DC, 2019)
This report contains the assessments of BAHTNET and TSD based on the PFMI. The assessment was undertaken in the context of the International Monetary Fund and World Bank Financial Sector Assessment Program (FSAP) of Thailand in November 2018. The assessors were Gynedi Srinivas and Dorothee Delort of the World Bank’s Payment Systems Development Group. The assessors would like to thank the Thai counterparts for their excellent cooperation and generous hospitality. The objective of the assessment was to identify potential risks related to the FMIs that may affect financial stability. While safe and efficient FMIs contribute to maintaining and promoting financial stability and economic growth, they may also concentrate risk. If not properly managed, FMIs can be sources of financial shocks, such as liquidity dislocations and credit losses, or a major channel through which these shocks are transmitted across domestic and international financial markets. The scope of the assessment includes two main FMIs as well as the authorities in Thailand responsible for regulation, supervision, and oversight of FMIs. BAHTNET and TSD are assessed against all relevant principles of the PFMI. The authorities, the BOT and the SEC, are assessed using the responsibilities for authorities of FMIs.